Validity and reliability of the patient assessment of constipation quality of life questionnaire for the Turkish population - Bengi, Göksel; Yalçın, Mustafa; Akpınar, Hale; Keskinoğlu, Pembe; Ellidokuz, Hülya (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: There are few specific evaluation forms for evaluating the quality of life among patients with chronic constipation. Our study aimed to determine the validity and reliability of the translated Patient Assessment of Constipation Quality of Life (PAC-QOL) questionnaire for the Turkish population because evidence of its reliability and validity is required to justify its use in other studies and clinical practice. Materials and Methods: This study included 154 patients with constipation who were treated at the Department of Gastroenterology, Dokuz Eylül University Hospital between January and June 2012. The translated PAC-QOL questionnaire was completed by patients at the clinic and also at a 2-week follow-up to test its reliability. Results: Cronbach’s alpha coefficient (internal consistency) was 0.91 (good) for the translated PAC-QOL questionnaire. Time validity was evaluated using the intraclass correlation coefficient (ICC) method, and the ICC value for all questions was confirmed as 0.68 at the 2-week follow-up. The validity of the tool in the study group was evaluated using factor analysis, and the results were highly significant (Kaiser–Meyer–Olkin value: 0.857; Bartlett’s test: p=0.001). Questions were categorized according to six factors based on the factor analysis, and these factors explained 65.1% of the total variation. For hypothesis verification of the tool, the correlation coefficient for PAC-QOL and PAC Symptoms (PAC-SYM) was r=0.577 (p<0.001), whereas the correlation coefficient for PAC-QOL and constipation severity score was r=0.457 (p<0.001). Conclusion: The PAC-QOL questionnaire was reliable, although not valid because of the limited sample group.